PENGEMBANGAN MEDIA PEMBELAJARAN MACROMEDIA FLASH 8 PADA MATA PELAJARAN PAI KELAS XI IPS 1 SMA NEGERI 1 GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Jamiatul Fitri; Sarmidin Sarmidin; Ikrima Mailani (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2019)
In the process student learning feel bored because teacher haven’t been able to develop media Macromedia flash 8 is well.and teachers less creative in learning media developing macromedia flash 8 so that learning is not interesting. Look at field condition. Reseacher interest for discuss with goals in order that can knowing macromedia flash 8 developing on study Islamic Religious Education that benefit and deficiency this macromedia flash 8. Researcher gathered data use questionnaire, interview, dan observation.Kind of research use R & D (Research and Development) research and development measures consist of studies about the research findings of a product to be developed, development of product, conducting a field test in keeping with background where the product is going to used. Analize data technique is quantitative descriptive.Based on the research results got that macromedia flash 8 development is very well qualified. Because validation result by materi expert and media expert is learning media development macromedia flash 8 at the value of the valid and not revision. The comparison of the old and new work systems is so vastly different in that old work system is valued at 31,52% and the new system 85,37% it is show that learning media development macromedia flash 8 is success.